2021
DOI: 10.1093/icvts/ivab067
|View full text |Cite
|
Sign up to set email alerts
|

Blunt traumatic thoracic aortic injuries: a retrospective cohort analysis of 2 decades of experience

Abstract: OBJECTIVES The aim of this study was to analyse and report the changes in the management of blunt traumatic aortic injuries (BTAIs) in a single centre during the last 2 decades. METHODS A retrospective analysis of all patients diagnosed with BTAI from January 1999 to January 2020 was performed. Data were collected from electronic/digitalized medical history records. RESULTS … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 18 publications
0
9
1
Order By: Relevance
“…A particular challenge in studying the longer-term course of endovascular interventions like TEVAR relates to high rates of lost to follow-up, particularly in young and otherwise healthy patients. The issue compounds over time as patients’ overall health continues to improve and they become increasingly less inclined to return for follow-up visits and surveillance imaging 25 26. As noted in several studies above, loss to follow-up rates of 30%–40% are not uncommon in this patient population, and some studies have reported that 37.6% of TEVAR-treated patients do not return for stent surveillance imaging 29.…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…A particular challenge in studying the longer-term course of endovascular interventions like TEVAR relates to high rates of lost to follow-up, particularly in young and otherwise healthy patients. The issue compounds over time as patients’ overall health continues to improve and they become increasingly less inclined to return for follow-up visits and surveillance imaging 25 26. As noted in several studies above, loss to follow-up rates of 30%–40% are not uncommon in this patient population, and some studies have reported that 37.6% of TEVAR-treated patients do not return for stent surveillance imaging 29.…”
Section: Discussionmentioning
confidence: 96%
“…Although limited by a loss to follow-up rate of 41%, they reported a 9.1% rate of death and only two minor endoleaks during the follow-up period 25. Prendes et al 26 followed 46 TEVAR patients for a median duration of 34 months, reporting a 93.3% survival rate and a 2.1% rate of late interventions. However, this study was also limited by a loss to follow-up rate of 43.2% 26…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…EVAR has been the first-line treatment for TAI according to the guidelines of the Society for Vascular Surgery (SVS) [2], the European Society of Cardiology [9], the Eastern Association for the Surgery of Trauma [10], and the European Society for Vascular Surgery (ESVS) [1], considering previously published reports of the low mortality and morbidity of EVAR compared with open surgery. Several studies including a relatively large number of cases with a long follow-up showed satisfactory outcomes of EVAR for TAI and superiority of EVAR over open surgery [3,5,6,[11][12][13]. However, EVAR for TAD was scarcely reported, and the characteristics of TAD were not thoroughly known.…”
Section: Discussionmentioning
confidence: 99%
“…Blunt aortic injury is most commonly observed after a sudden deceleration, usually in a car accident. Other causes include motorcycle, aircraft, car, and pedestrian collisions; falls; and crush injuries (5,6,7,8). Approximately 80% of patients died before hospital arrival, and most of the deaths occurred within the rst hour of hospital arrival (2,3,9).…”
Section: Introductionmentioning
confidence: 99%